2009
DOI: 10.1007/s12040-009-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

A case study of atmospheric boundary layer features during winter over a tropical inland station — Kharagpur (22.32°N, 87.32°E)

Abstract: The local weather and air quality over a region are greatly influenced by the atmospheric boundary layer (ABL) structure and dynamics. ABL characteristics were measured using a tethered balloon-sonde system over Kharagpur (22.32 • N, 87.32 • E, 40 m above MSL), India, for the period 7 December 2004 to 30 December 2004, as a part of the Indian Space Research OrganizationGeosphere Biosphere Program (ISRO-GBP) Aerosol Land Campaign II. High-resolution data of pressure, temperature, humidity, wind speed and wind d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In monsoon, the strong prevailing winds disperse the pollutants quickly and get them washed out by precipitation. In contrast to this, both winds and ABL depth are low over Indian subcontinent by which the pollutants get trapped during winter (Alappattu et al, 2009). The daytime average low O 3 mixing ratio (10.81 ± 3.84 ppbv) observed in July was mainly due to the intense south-west monsoon which washes out pollution over this location.…”
Section: Diurnal Variation and Rate Of Change Of O 3 During Differentmentioning
confidence: 77%
“…In monsoon, the strong prevailing winds disperse the pollutants quickly and get them washed out by precipitation. In contrast to this, both winds and ABL depth are low over Indian subcontinent by which the pollutants get trapped during winter (Alappattu et al, 2009). The daytime average low O 3 mixing ratio (10.81 ± 3.84 ppbv) observed in July was mainly due to the intense south-west monsoon which washes out pollution over this location.…”
Section: Diurnal Variation and Rate Of Change Of O 3 During Differentmentioning
confidence: 77%
“…Viswanadham and Pinaka Pani (1994) have reported alarmingly low morning V Cs over north India, the worst season being October followed by January. Alappattu et al (2009) studied the ABL features over Kharagpur (22.32 • N,87.32 • E) and found that in general, V C was low during the morning and evening hours and maximum during the early afternoon hours. The lowest V C values observed corresponded with significantly low wind speeds and high aerosol mass concentrations.…”
Section: Long-term Trends In Ventilation Coefficient (Vc)mentioning
confidence: 99%
“…Several researchers, viz., Padmanabhamurthy and Mandal (1979), Alappattu et al (2009) etc., have studied the assimilative capacity, dispersal capacity and pollution potential in terms of the variations in ventilation coefficients over different locations in India. However, they are limited to short periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant because there can be significant local contributions to the BC mass concentration. Moreover, the cause of the morning peak in the diurnal cycle is attributed to fumigation due to an increasing mixing layer (Devara and Raj, 1983;Alapattu et al, 2009;Mahalakshmi et al, 2011) which brings polluted air from aloft down to the surface. This is a reasonable assumption in a remote area with little to no local emissions.…”
Section: Diurnal Variations Of Bc Mass Concentrationmentioning
confidence: 99%